PENGGUNAAN BILYET GIRO KOSONG SEBAGAI ALAT PEMBAYARAN DAN UPAYA MENGATASINYA - Anik Tyaswati WL (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
The use of a bank draft instrument as a means of payment in Indonesia is still very attractive in terms of the nominal value of the high turnover giro. Payment by giro is relatively safe and convenient than using cash. But in practice can not be separated from the problem of default risk as a result of a bank draft that is not provided in sufficient funds by towing or known as giro empty. One of the efforts made by Bank Indonesia to prevent the circulation of an empty bank draft, among others, the implementation of the policy is the imposition of sanctions proportional either through the establishment of more stringent criteria of the effectiveness of the sanctions or to provide coverage broader become nationally by issuing Bank Indonesia Regulation No. 8 / 29 / PBI / 2006 on National Black List Puller Checks and / or Giro Blank and Bank Indonesia Circular Letter No. 9/13 / DASP dated June 19, 2007 regarding the National Towing Blacklist Check and / or Giro Blank.